2020
DOI: 10.1113/jp279045
|View full text |Cite
|
Sign up to set email alerts
|

Local sleep spindles in the human thalamus

Abstract: Key points Sleep spindles have recently been shown to occur not only across multiple neocortical regions but also locally in restricted cortical areas. Here we show that local spindles are indeed present in the human posterior thalamus. Thalamic local spindles had lower spectral power than non‐local ones. While non‐local thalamic spindles had equal local and non‐local cortical counterparts, local thalamic spindles had significantly more local cortical counterparts (i.e. occurring in a single cortical site). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 61 publications
8
23
0
Order By: Relevance
“…Although thalamocortical circuit dysfunction has previously been implicated in the pathophysiology of generalized seizures in absence epilepsy (Williams, 1953;Beenhakker and Huguenard, 2009;Maheshwari and Noebels, 2014;Fogerson and Huguenard, 2016), our observation of a focal spindle deficit in CECTS reveals that thalamocortical circuit can be focally disrupted in epilepsy. Consistent with this, prior work has demonstrated that distinct thalamocortical assemblages generate focal spindles (Andersen et al, 1967;Bastuji et al, 2020), and these distinct circuits can promote focal abnormalities (Fogerson and Huguenard, 2016;Clemente-Perez et al, 2017). In particular, sensorimotor thalamocortical circuits promote spatially distinct spindle populations (Nishida and Walker, 2007;Fogerson and Huguenard, 2016), and these sensorimotor spindles have been mechanistically tied to focal seizures in mouse models (Clemente-Perez et al, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…Although thalamocortical circuit dysfunction has previously been implicated in the pathophysiology of generalized seizures in absence epilepsy (Williams, 1953;Beenhakker and Huguenard, 2009;Maheshwari and Noebels, 2014;Fogerson and Huguenard, 2016), our observation of a focal spindle deficit in CECTS reveals that thalamocortical circuit can be focally disrupted in epilepsy. Consistent with this, prior work has demonstrated that distinct thalamocortical assemblages generate focal spindles (Andersen et al, 1967;Bastuji et al, 2020), and these distinct circuits can promote focal abnormalities (Fogerson and Huguenard, 2016;Clemente-Perez et al, 2017). In particular, sensorimotor thalamocortical circuits promote spatially distinct spindle populations (Nishida and Walker, 2007;Fogerson and Huguenard, 2016), and these sensorimotor spindles have been mechanistically tied to focal seizures in mouse models (Clemente-Perez et al, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…The simplest possibility is that TFσ peaks are generated by the exact same mechanism as spindles and that any differences are purely a consequence of selection bias. Spindle power measured at the scalp can vary with the degree with which a spindle is local or global [ 50 , 51 ]. Alternatively, high-powered spindles emanating from cortical locations more distant from the recording electrode might appear to be weaker when propagated via volume conduction [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IEDs in the human thalamus, such as in the ANT LFP records were observed and suggested the involvement of ANT in the propagation of epileptic activity and to contribute to the epileptic network (Hodaie et al, 2002; Sweeney-Reed et al, 2016). In several former studies, sleep spindles were recorded from the human thalamic nuclei, including the ANT and the posterior thalamus/medial pulvinar nucleus of epilepsy patients undergoing DBS or invasive presurgical neurophysiological investigation (Bastuji et al, 2020; Mak-Mccully et al, 2017; Tsai et al, 2010). Here we investigated the association between thalamic sleep spindles, interictal epileptiform discharges, ripples, and their associations with intellectual ability within two higher-order thalamic nuclei in human subjects, the ANT and the MD.…”
Section: Introductionmentioning
confidence: 99%